Wind hazard in peninsular Malaysia: level of awareness - MUHAMMAD SYAMIM, EMBONG (2013)
Wind hazard risks in Malaysia due to windstorm are increase rapidly. From the record it shows that number of buildings structure damage and failure mostly due to thunderstorm. Awareness among Malaysian needs to conduct to ensure the level of knowledge regarding wind hazard. Survey was conducted to indicate the level of awareness and knowledge. Result shown that public awareness are low and not well notified about wind hazard. While for constructor and engineers, there are notified the wind hazard. However the implementations in design are not given prioritized. For that, it can conclude that level of awareness among Malaysian mostly still low